The Influence of Near Work and Time Spent Outdoors on Refractive Error and Axial Length in Indian Children. - Ramamurthy, Dharani; Radhakrishnan, Hema (Optometry & Visual Performance, 2019)
Background: Myopia is a complex, multifactorial disorder with interplay between genetic and environmental factors. Less time spent outdoors and increased near-work are the potential environmental risk factors for myopia. No study so far has examined the associations between time spent on near work and outdoor activity on myopic refractive error and axial length in Indian children. Methods: 151 subjects aged 10 to 17 years were enrolled. Subjects were divided into myopes (SER: -0.50 D or more) and non-myopes (SER: -0.25 D to +2.OO D). Refractive error was measured objectively by retinoscopy with and without cycloplegia, and axial length was measured using an A-scan biometer. Near work and outdoor activities were assessed using a validated questionnaire. Results: Subjects were divided into four groups based around their near work, using an 18-diopter hour (Dh)/day cut-off, and their outdoor activity time, with a 1-hour/day cutoff (Less Near work More Outdoor; Less Near work Less Outdoor; More Near work More Outdoor; More Near work Less Outdoor). A statistically significant interaction (p<0.05) was shown with near work activity and outdoor time for both refractive error and axial length. The group with more near work and less time spent outdoors showed significantly (p<0.05) more myopia and longer axial length compared to the group who spent less time on near work and more time outdoors. Conclusion: Children who spent more time on near work and less time on outdoors had significantly more myopic refraction and longer axial length compared to those who performed less near work and spent more time outdoors. Our study highlights the importance of reducing near work and increasing outdoor activity in order to reduce the risk of myopia.